2013
DOI: 10.1111/jce.12197
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cheyne‐Stokes Respiration Reduces Arrhythmic Events in Chronic Heart Failure

Abstract: This study demonstrates a decrease of appropriate defibrillator therapies by ASV treated CSR in patients with CHF and ICD. A reduced exposure to hyperventilation, hypoxia, and improvement in indices of CHF severity and neurohumoral disarrangements are potential causative mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 43 publications
0
23
0
5
Order By: Relevance
“…118 Several short-term randomized controlled trials have evaluated the effects of ASV on CSA severity and LV function ( Table 2). Although these studies show that ASV abolishes CSA, its effects on LVEF are inconsistent.…”
Section: Csamentioning
confidence: 99%
“…118 Several short-term randomized controlled trials have evaluated the effects of ASV on CSA severity and LV function ( Table 2). Although these studies show that ASV abolishes CSA, its effects on LVEF are inconsistent.…”
Section: Csamentioning
confidence: 99%
“…2) [90]. Subsequently, observational data showed that treatment of CSA using adaptive servo-ventilation (ASV) therapy was associated with a decrease of malignant arrhythmic events [91].…”
Section: Premature Atrial or Ventricular Complexesmentioning
confidence: 99%
“…23 Finally, a study by Bitter et al could not be included in the meta-analysis because no standard deviations were provided, but demonstrated a small increase in LVEF with ASV. 6 (see Figure S1) apnea-Hypopnea index: Twenty-six studies 5,[29][30][31][32] reported data on the effects of ASV on AHI and were consistent in showing that ASV improves AHI over baseline. Meta-analyses indicate that ASV decreases AHI by 30 events/h (95% CI: −27 to −34 events/h) over baseline.…”
Section: -32mentioning
confidence: 80%
“…Finally, studies by Bitter et al, Cowie et al and Morgenthaler et al could not be included in the meta-analysis because they did not provide standard deviation, but demonstrated a normalization of AHI with ASV. 2,6,28 (see supplemental material, Figure S2) MortaLity (cardiac deatH): Four studies 2,12-14 reported data on mortality in CHF patients using ASV compared to standard care. Cowie et al…”
Section: -32mentioning
confidence: 99%